DAMPAK FRAMING KASUS KEKERASAN REMAJA SANTRI PADA MASYARAKAT ROGOJAMPI KABUPATEN BANYUWANGI - Mita Ayu Hidayatullah; Nur Ainiyah (Fakultas Dakwah Universitas Ibrahimy, 2025)
Research to describe the impact of news framing of cases of violence among Islamic boarding school students on the Banyuwangi community. Current technological developments greatly influence the role of the mass media. Along with the development of the mass media, it seems that there is never a vacuum in informing news. The mass media is actually in the midst of a social reality that has various interests, conflicts, and different facts. In addition to conveying news, the mass media also has the ability to act as an institution that can shape public opinion. Like the news circulating in February 2024 which stated that there was violence among adolescent students at Islamic boarding schools. Public comments on the news accessed through the media play a very active role in the progress of the development of information circulating in the community, making the news packaged so attractive that the public feels that their information needs are met. This study uses a qualitative research method with a case study type of research. The results of the study show that several impacts that occurred in the Banyuwangi community due to the publication of news of violence that occurred among adolescent students, namely: 1) The impact of news framing of cases of violence has caused many public opinions about Islamic boarding school violence 2) Raising a sense of worry in some people to send their sons or daughters to Islamic boarding schools. 3) Some people are becoming selective in choosing Islamic boarding schools.